Meat quality parameters of five muscles of Holando steers during post-mortem ageing: II Color evolution during storage - Franco, J.; Feed, O.; Bianchi, G.; Garibotto, G.; Ballesteros, F.; Nan, F.; Percovich, M.; Piriz, M.; Bentancur, O. (Agrociencia Uruguay, 2008)
The objective of this study was to assess the effect of the muscle type, Gluteo biceps, (GB), Longissimus dorsi (LD) Psoas (PS), Semimembranosus (SM) and Semitendinosus (ST) on meat color evolution parameters after 7 days oxygen - exposed samples. During the 7 days of aerobic post-mortem storage, the samples showed a gradual decrease color (C*) (day 1: 27,0 vs. day 7: 24,1) with the lowest values at day 5 (23, 7) (P d» 0,001), a reduction in a*(redness) values with significant differences between day 1 and 4 (21,9 vs. 18,8), and an increment in Hue values (H*) (day 1 35,6 vs. day 7: 41,3) (P≤ 0,001). During the storage period color parameters had a muscle x day significant interaction effect (P≤ 0.0001). ST showed the greatest values of luminosity (L*), red index (a*) and Color index (C*) related to other muscles evaluated, with the exception of SM that reached the same values at day 6 of storage. Hue (H*) values increased during the storage period with GB and PS, reaching the greatest values at day 7. These results suggest different strategies of sale depending on the type of cut, especially if the system of packing is permeable to the oxygen. The indication in the trays with the date of packing, indicating the period during which the color does not suffer major alterations, appear as advisable practices of marketing, depending on the decisive importance of this characteristic in the decision of purchase.